Management of Inflammatory Bowel Disease during Pregnancy and Breastfeeding Varies Widely: A Need for Further Education - Vivian Wai-Mei Huang; Hsiu-Ju Chang; Karen Ivy Kroeker; Karen Jean Goodman; Kathleen M. Hegadoren; Levinus Albert Dieleman; Richard Neil Fedorak (Canadian Journal of Gastroenterology and Hepatology)
Background. Inflammatory bowel disease (IBD) affects patients in their young reproductive years. Women with IBD require maintenance therapies during pregnancy and breastfeeding. However, physician management of IBD during pregnancy and breastfeeding has not been well characterized. Objective. To characterize physician perceptions and management of IBD during pregnancy and breastfeeding. Methods. A cross-sectional survey of Canadian physicians who are involved in the care of women with IBD was conducted. The survey included multiple-choice and Likert scale questions about perceptions and practice patterns regarding the management of IBD during pregnancy and breastfeeding. Results. 183 practicing physicians completed the questionnaire: 97/183 (53.0%) gastroenterologists; 75/183 (41.0%) general practitioners; and 11/183 (6.0%) other physicians. Almost half (87/183, 47.5%) of the physicians felt comfortable managing pregnant IBD patients. For specified IBD medications, proportions of physicians who indicated they would continue them during pregnancy were as follows: sulfasalazine, 47.4%; oral mesalamine, 67.0%; topical mesalamine, 70.3%; oral prednisone, 68.0%; topical prednisone, 78.0%; oral budesonide, 61.6%; topical budesonide, 75.0%; ciprofloxacin, 15.3%; metronidazole, 31.4%; azathioprine, 57.1%; methotrexate, 2.8%; infliximab, 55.6%; adalimumab, 78.1%. Similar proportions of physicians would continue these medications during breastfeeding. A higher proportion of gastroenterologists than nongastroenterologists indicated appropriate use of these IBD medications during pregnancy and breastfeeding. Conclusions. Physician management of IBD during pregnancy and breastfeeding varies widely. Relative to other physicians, responses of gastroenterologists more frequently reflected best practices pertaining to medications for control of IBD during pregnancy and breastfeeding. There is a need for further education regarding the management of IBD during pregnancy and breastfeeding.